Peran Dukungan Sosial Orang Tua Terhadap Intensi Studi Lanjut ke Perguruan Tinggi di Kota Gunungitoli - Senikariawati Laiya; Tarmidi; Sri Supriyantini (Psychopolytan : Jurnal Psikologi, 2025)
Higher education participation in Indonesia remains relatively low, making it important to examine factors that may influence students’ intentions to continue their studies. The intention to pursue higher education is considered an early indicator of students’ decisions to actually enroll in university. This study aims to examine the role of parental social support in shaping students’ intentions to pursue higher education. The research sample consisted of 306 secondary school students selected using purposive sampling. Data were collected through a parental social support scale and a higher education intention scale. The results showed that parental social support had a significant effect on students’ intentions to pursue higher education, with a significance value of 0.001 and a correlation coefficient of r = 0.11, thus confirming the hypothesis. These findings emphasize that parental social support is an external factor that contributes to strengthening students’ intentions to continue their studies at the higher education level.